Counselling in schools - Bor, Robert (London ; Thousand Oaks, Calif. : SAGE, 2002)
This text is a practical, contemporary guide to providing effective counselling support within school settings. It is an invaluable resource for anyone wishing to provide counselling support for pupils in secondary education.
Introduction; Setting the Scene; An Overview of Working as a Counsellor with Young Children; Theory of Solution-Focused Counselling in the School Setting; Aims and Structure of the Counselling Session; Overview of Essential Counselling Skills; Brief and Positive Counselling Interventions with Pupils; Legal and Confidentiality Issues in Counselling Children; Schools and Trauma; Preparation, Response and Recovery; Setting Up and Maintaining a School Counselling Service; Evaluating Counselling in a School Setting; Confidentiality; Counselling and the Law; Confidentiality Guidelines for College Counsellors in Further Education and Sixth Form Colleges; Guidelines for University and College Counselling Services 1998; Bullying and Harrassment; Policy and Guidelines; Genogram Symbols; Access to Records of Counselling and Psychotherapy.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Counseling in secondary education -- Great Britain; Educational counseling -- Great Britain; Counseling in secondary education; Educational counseling; Services personnels aux élèves du secondaire; Orientation scolaire; Services personnels aux élèves du secondaire -- Grande-Bretagne.; EDUCATION -- Counseling -- General; Counseling in secondary education; Educational counseling; Great Britain; Conseiller d'orientation.; Enseignement secondaire; Orientation scolaire; Pratique professionnelle; Royaume-Uni.; Guide (Descripteur de forme)